2017
DOI: 10.1016/j.phro.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic resonance imaging-based approach to quantify radiation-induced normal tissue injuries applied to trismus in head and neck cancer

Abstract: Background and Purpose In this study we investigated the ability of textures from T1-weighted MRI scans post-contrast (T1wpost) to identify the critical muscle(s) for radiation-induced trismus. Materials and Methods The study included ten cases (Trismus: ≥Grade 1), and ten age-sex-tumor-location-and-stage-matched controls treated with intensity-modulated radiotherapy to 70Gy@2.12Gy in 2005–2009. Trismus status and T1wPost were conducted within one year post-radiotherapy. For the masseter, lateral and medial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
(51 reference statements)
0
23
0
Order By: Relevance
“…Only four studies (25%) derived texture features from a single MRI sequence. Thor et al ( 45 ) extracted 24 textures, containing first- and second-order features, from T1-weighted post-contrast images to quantify radiation-induced trismus. Brown et al ( 36 ) investigated whether 21 texture features from a set of 300 DWI MRI parameters could reliably predict histopathological classification of thyroid tumors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only four studies (25%) derived texture features from a single MRI sequence. Thor et al ( 45 ) extracted 24 textures, containing first- and second-order features, from T1-weighted post-contrast images to quantify radiation-induced trismus. Brown et al ( 36 ) investigated whether 21 texture features from a set of 300 DWI MRI parameters could reliably predict histopathological classification of thyroid tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic resonance imaging radiomics is not limited to studies of tumors alone. Radiomic signatures can predict RT-related toxicities in normal tissues, such as radiation-induced trismus ( 45 ), or they can be designed to autosegment parotid glands post-RT ( 46 ). Future studies should investigate whether radiomic features could predict the effects of RT-related toxicities on quality of life or if changes in corresponding critical organ volumes, such as structures involved in the swallowing mechanism, can be estimated.…”
Section: Discussionmentioning
confidence: 99%
“…88 A more limited number of studies has also shown potentially useful preliminary results for CT-based prediction of radiationinduced changes in breast tissue during accelerated partial breast irradiation, 89 sensorineural hearing loss in HNC radiochemotherapy 90 ; and for MRI-based prediction of trismus in HNC RT. 91 The potential advantages of general radiomic-based textural analysis to predict toxicity are therefore wideranging and need further investigation in order to be extended into the physicians' practice. This would help to select patients who will benefit most from highly conformational and/or adaptive RT, e.g.…”
Section: Bjr|openmentioning
confidence: 99%
“…In recent years, the analysis of anatomic MRI, such as T2w and T1-w MRI, with and without contrast agent (CA) injection, has been carried out in some studies to assess radiationinduced effects in muscles, especially after radiotherapy for head and neck cancer (HNC). [17][18][19] Pelvic floor muscles were qualitatively evaluated before and after prostate cancer radiotherapy, focusing, in particular, on internal obturator muscles and levator ani muscles. 20 MRI findings revealed an increase in T2-w signal and T1-w contrast enhancement, compatible with a radiation-induced inflammation.…”
Section: Introductionmentioning
confidence: 99%